Ichthyosis Fetalis in a Lacaune Lamb - Arman Shokri; Afshin Raoofi; Sara Shokrpoor (Veterinary Medicine and Science)
ABSTRACT Ichthyosis (inherited congenital condition) is a heterogeneous group of skin cornification and keratinization disorders. Ichthyosis can affect animal and human and characterized by an excessive amount of superficial scale on the skin. A male Lacaune lamb was born alive from a primiparous ewe but it was unable to stand and it was in lateral recumbency and died 12 h after birth. Skin abnormalities included all over hyperkeratosis, cracking in some parts of the body like head and neck. In histopathological investigation of the cutaneous lesions, there was moderate‐to‐severe thickening of the stratum corneum, with a compact and laminated pattern of orthokeratotic hyperkeratosis, whereas no abnormalities were observed in the other layers of the epidermis. Ichthyosis was diagnosed on the basis of clinical and histopathological findings. In conclusion, ichthyosis in lambs can occur in different forms, but further studies and investigations are needed to accurate classification of this condition in lamb.